Az agrárkonjunktúra hatása a nagykanizsai uradalom erdőgazdálkodására : 1850-1914 - Kaposi, Zoltán (Közép-Európai Közlemények, 2012)
This study is about the economic modernisation of the Manor of Nagykanizsa (5800 hectare). The Manor of Nagykanizsa was the property of the Prince-Batthyány family for more than 200 years. There was an agricultural boom in 1850-80 in Hungary. During this period the agricultural production increased while the grain strengthened its mono cultural position. In these years the profit maximisation took a central place in the officers’ thinking. According to this, a size of 1140 hectare of wood around Nagykanizsa was cut off in 1871–72. The forestry of the manor was controlled by excellent, qualified forest engineers. This released area was used for grain production and livestock. The conversion of forestry had several impacts. It modified the lifestyle of the local society; meanwhile, at the remaining parts it created a professional, country4famous forestry. It was also an important income source of the actual landlord.